FAKTOR-FAKTOR PENENTU MUTU PENDIDIKAN DI INDONESIA: SINTESIS SYSTEMATIC LITERATURE REVIEW - Titin Supriyatin; Roida Eva Flora Siagian; Deni Nasir Ahmad; Suhendra Suhendra (Jurnal Manajemen Pendidikan, 2026)
This study examines the factors that influence the quality of education in Indonesia through a Systematic Literature Review (SLR) approach. From 49 initial articles obtained using Publish or Perish, 13 articles met the inclusion criteria and were analyzed further. The thematic analysis identified five dominant themes, namely principal leadership, teacher performance and competence, strategic management of educational institutions, quality assurance and educational policy, as well as curriculum, organizational culture, and internal inhibiting factors. The findings indicate that leadership and school governance are key drivers in improving educational quality, while teachers play a strategic role in ensuring the quality of the learning process. Quality assurance systems and consistent policy implementation are also proven to be essential for achieving sustainable improvement. This study emphasizes that improving the quality of education can only be achieved through an integrated approach, which includes strengthening leadership, implementing effective school management, developing teacher professionalism, and fostering an organizational culture that supports quality. These findings provide a strong conceptual foundation for researchers, practitioners, and policymakers in designing strategies to improve the quality of education across various levels and contexts in Indonesia.